STUDENTS' DIFFICULTIES IN ANSWERING MULTIPLE-CHOICE QUESTIONS IN NARRATIVE TEXTS - Reyli Nuary Reda Prahara, - (2010)
Reading strategies become the most dominant factors in students' success in Ujian Nasional (UN) for English subject so the research was conducted to find the students difficulties in an UN-like task in form of multiple-choices focusing on narrative texts. The research was conducted at a bimbingan belajar in Bandung involving 20 students from seven junior high schools in Bandung. The instruments were task-giving and short interviews. The task-giving demanded main idea, detailed information, implied information, word reference, word meaning, jumbled sentences arrangement, and paragraph completion. The result was vocabulary mastery as the main problem. Hence, more vocabulary teaching is suggested.